Risk, Reward, and Resistance: Navigating Work and Family under Hungary's New Pronatalism. (15th September 2022) - Glass, Christy; Fodor, Éva
Abstract: New pronatalist regimes rely on market incentives to increase childbearing and encourage full employment. Few countries have instituted a more extreme version of new pronatalism than Hungary. The current study analyzes how professional women navigate uncertainty and risk under Hungary's pronatalist regime. Our analysis of twenty-one in-depth interviews with middle-class professional women reveals inherent tensions and contradictions. Respondents perceived two competing imperatives: seek financial security in a highly unstable labor market and privately absorb care burdens associated with larger families. Respondents weighed the potential rewards of accessing various pronatalist benefits against the costs of reproduction in a policy context characterized by risk and uncertainty. Respondents were highly selective regarding which benefits they accessed and which they avoided. Our analysis contributes to research and theory on the substantive impact of formal welfare and work policies, including the ways actors interpret and engage policies in order to limit risk and uncertainty.